A putative bifunctional CPD/ (6-4) photolyase from the cyanobacteria Synechococcus sp. PCC 7335 is encoded by a UV-B inducible operon: New insights into the evolution of photolyases - Fernández, María Belén; Latorre, Lucas; Correa-Aragunde, Natalia; Cassia, Raúl (Frontiers in Microbiology, 2022)
Photosynthetic organisms are continuously exposed to solar ultraviolet radiation-B (UV-B) because of their autotrophic lifestyle. UV-B provokes DNA damage, such as cyclobutane pyrimidine dimers (CPD) or pyrimidine (6-4) pyrimidone photoproducts (6-4 PPs). The cryptochrome/ photolyase family (CPF) comprises flavoproteins that can bind damaged or undamaged DNA. Photolyases (PHRs) are enzymes that repair either CPDs or 6-4 PPs. A natural bifunctional CPD/(6-4)- PHR (PhrSph98) was recently isolated from the UV-resistant bacteria Sphingomonas UV9. In this work, phylogenetic studies of bifunctional CPD/(6-4)- photolyases and their evolutionary relationship with other CPF members were performed. Amino acids involved in electron transfer and binding to FAD cofactor and DNA lesions were conserved in proteins from proteobacteria, planctomycete, bacteroidete, acidobacteria and cyanobacteria clades. Genome analysis revealed that the cyanobacteria Synechococcus sp. PCC 7335 encodes a two-gene assembly operon coding for a PHR and a bifunctional CPD/(6-4) PHR- like. Operon structure was validated by RT-qPCR analysis and the polycistronic transcript accumulated after 15 minutes of UV-B irradiation. Conservation of structure and evolution is discussed. This study provides evidence for a UV-B inducible PHRs operon that encodes a CPD/(6-4)- photolyase homolog with a putative bifunctional role in the repair of CPDs and 6-4 PPs damages in oxygenic photosynthetic organisms.